FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN TERHADAP PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Wijaya, Laurensius; Iskak, Jamaludin (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to find out how the influence of Profitability, Liquidity, Leverage, and Company Size on firm value in manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The sample was selected by purposive sampling method and the valid data were 55 companies. The data processing technique uses multiple regression analysis assisted by the E-views 9 program and Microsoft Excel 2016. The results of this study indicate that profitability has a significant effect on firm value, while liquidity has a negative and insignificant effect on firm value, leverage and firm size are positive and not significant to firm value.